PP.26.03: PREVALENCE AND FACTORS ASSOCIATED WITH RESISTANT HYPERTENSION IN PRIMARY CARE PRACTICES. (June 2015) - Park, C.; Lee, K.; Lee, S.; Kim, E.; Seo, H.; Park, S.; Kim, J.; Rha, S.; Oh, D.
Abstract : Objective: The purpose of this study was to investigate the prevalence and clinical and metabolic risk factors of resistant hypertension (RH) in Korean hypertensive patients treated by primary care physicians. Design and method: A total of 3109 hypertensive patients were analyzed. The mean age was 62.3 ± 11.3 years, and 1502 (48.3%) of the participants were male. All hypertensive patients with>2 recorded BP measurement during a minimum period of 6 months was identified. Patients were considered uncontrolled if their most recent BP during the study period were systolic BP > 140mmHg or diastolic BP > 90mmHg. Uncontrolled patients taking > 3 therapy classes including diuretics or controlled patients taking > 4 therapy classes were regarded as RH. Results: Uncontrolled BP was found 30.9% (SBP alone 25.7%, DBP alone 11.4%, Both SBP and DBP 6.3%). Overall, 26.3% of uncontrolled patients were RH. The prevalence of RH were 8.1%. Patients with RH were characterized by a significantly higher number of male (54.8%, P = 0.033), and showed significantly higher body weight, waist circumstance (65.9% vs 34.1%, p = 0.002), and smoker (p = 0.01) compared with non-RH hypertension. Patients with RH also showed significantly higher multicomorbidity (including dyslipidemia, LVH, impaired renal function, and cardiovascular disease) compared with patients with non—RH hypertension. Conclusions: The results of this community based study indicate considerable number of hypertensive patients treated by primary care physician are maintained as uncontrolled or resistant status. Therefore, more aggressive interventions and referral to hypertension specialist are needed to patients with uncontrolled or RH treated in community.